2016
DOI: 10.1109/tsp.2016.2539140
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Detection of Point-Like Targets in Spectrally Symmetric Interference

Abstract: Abstract-We address adaptive radar detection of targets embedded in ground clutter dominated environments characterized by a symmetrically structured power spectral density. At the design stage, we leverage on the spectrum symmetry for the interference to come up with decision schemes capable of capitalizing the a-priori information on the covariance structure. To this end, we prove that the detection problem at hand can be formulated in terms of real variables and, then, we apply design procedures relying on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…When H 2 is assumed, the ICM is unstructured and real. Thus, following the lead of [5], we use the following estimates…”
Section: A Mos Decision Rules Using the Entire Data Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…When H 2 is assumed, the ICM is unstructured and real. Thus, following the lead of [5], we use the following estimates…”
Section: A Mos Decision Rules Using the Entire Data Matrixmentioning
confidence: 99%
“…For each of the mentioned scenarios, there exist examples of adaptive detectors in the literature [4], [5], [31]. The knowledge about the environment as well as the structure of the ICM can guide the system operator towards the most appropriate decision scheme.…”
Section: Introduction Motivation and Problem Formulationmentioning
confidence: 99%
“…These algorithms allow us to reduce the number of training samples required for the ICM estimation [16]- [23], [27], [28] by almost a half while maintaining a satisfactory detection performance. Further examples are provided in [24], [25], where it is shown that the spectral symmetry of the clutter can be used for instance to obtain gains of about 3 dB (in SINR, namely Signal-to-Interference plus Noise Ratio), for a Probability of Detection P d = 0.9 and Probability of False Alarm P f a = 10 −4 , in comparison to conventional detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the reflectivity change with grazing angles and the inaccurate registering of the terrain data would degrade its performance. Additionally, the persymmetric structure of the interference covariance matrix and the symmetric property of power spectral density of the clutter can also be used as priori knowledges to improve the detection performances in training-limited scenarios [17][18][19][20]. And some STAP detection methods, which allow one to identify the degree of accuracy of the prior knowledge and combine the prior information with the secondary data in an appropriate way, were proposed in [21,22].…”
Section: Introductionmentioning
confidence: 99%